2002
DOI: 10.1098/rspb.2002.2126
|View full text |Cite
|
Sign up to set email alerts
|

Multiple glacial refugia in the North American Arctic: inference from phylogeography of the collared lemming (Dicrostonyx groenlandicus)

Abstract: Cryptic northern refugia beyond the ice limit of the Pleistocene glaciations may have had significant influence on the current pattern of biodiversity in Arctic regions. In order to evaluate whether northern glacial refugia existed in the Canadian Arctic, we examined mitochondrial DNA phylogeography in the northernmost species of rodents, the collared lemming (Dicrostonyx groenlandicus) sampled across its range of distribution in the North American Arctic and Greenland. The division of the collared lemming int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 38 publications
11
121
1
1
Order By: Relevance
“…As more Beringian lineages are examined, we expect that more of these high-latitude cryptic refugia will be found (e.g. Fedorov and Stenseth, 2002) and that further genetic corroboration will be obtained for those already revealed.…”
Section: High Latitude Biodiversity and Cryptic Refugiamentioning
confidence: 99%
“…As more Beringian lineages are examined, we expect that more of these high-latitude cryptic refugia will be found (e.g. Fedorov and Stenseth, 2002) and that further genetic corroboration will be obtained for those already revealed.…”
Section: High Latitude Biodiversity and Cryptic Refugiamentioning
confidence: 99%
“…As a consequence, the Arctic tundra biome is of conservation concern because non-migratory species associated with this relatively young and depauperate biome are adapted to cold environments that have prevailed at high latitudes through much of the Quaternary (2.6 Myr; Abbott andBrochmann 2003, Callaghan et al 2004). Historical biogeographic studies revealed that Arctic species persisted in refugial areas through previous climatic warm phases (e.g., Fedorov and Stenseth 2002, Abbott and Brochmann 2003, Brunhoff et al 2003, Hewitt 2004, Hope et al 2013a), but continued persistence under current climate trends may depend on our ability to locate and accommodate refugial regions for Arctic biodiversity in an increasingly anthropic landscape (Chapin et al 2006, Kuemmerle et al 2014, Raynolds et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…However, questions have persisted regarding the existence of additional smaller refugia in the North and their relative contributions to diversity and post-glacial colonization (Fedorov and Stenseth 2002;Fleming and Cook 2002;Shafer et al 2010). For example, divergent genetic lineages endemic to Beringia were found Fedorov and Stenseth 2002;Brunhoff et al 2003;Fedorov et al 2003) in the collared lemming (Dicrostonyx), brown lemming (Lemmus), and tundra vole (Microtus oeconomus), a finding that (Table 2). Black arrows denote expected movement during cold periods of glacial maxima when sea levels were lower, while white arrows depict general pathways of colonization during warmer interglacials.…”
Section: Discussionmentioning
confidence: 85%
“…5) that help interpret the impact of the boundaries of the Beringian refugium, such as the Upper Kolyma region of Siberia in the west (e.g., Galbreath and Cook 2004;Kohli et al 2015;Haukisalmi et al 2016) and near the YukonAlaska border in the east (Dawson et al 2014). In addition, the influence of smaller peripheral refugia in the Canadian Arctic (Fedorov and Stenseth 2002;Fedorov et al 2003;Cook et al 2016b), southeast Alaska Sawyer and Cook 2016), and in the periglacial zone south of the Laurentide and Cordilleran ice sheets ) is being explored. Early attempts to unravel the evolutionary history of arctic ground squirrels (Urocitellus parryii), one of the quintessential high-latitude mammals, relied on a view of Beringia as a vast steppe with few natural barriers to gene flow (e.g., Nadler and Hoffmann 1977).…”
Section: Discussionmentioning
confidence: 99%